É o algoritmo, estúpido : como os softwares provocam alterações no conceito de newsmaking - Gomes Júnior, Paulo Pinheiro (2017)
The thesis analyzes the emergence of a new category of newsmaking caused by the influence of the Facebook’s algorithm. The amount of interactions carried out by the internet affects the list of incoming news. To understand the performance of this algorithm on the news it was conducted an interview with editors of Zero Hora’s page in the social network. It turned out then that there is no guarantee that the users actually see the whole content produced by the newspaper. The editors estimate that approximately only 5 % of the page followers will end up being aware of the posts that have been published by Zero Hora. In research conducted with the creation of a Facebook user the thesis found that there is a difference between news-values and algorithm values.